Synthesis, Characterization and Biological Activity of New Oleander Complexes against Bacteria Found in Polluted Water - Zainab Sabeer Abdulsada; Sahar Sabeeh Hassan; Sanaa Hitur Awad (Universitas Gadjah Mada, 2023)
Natural polymers are often non-toxic, biodegradable, biocompatible, and safe. A novel ligand was synthesized as a natural polymer using chitosan and oleander plant extract [(2R,3S,4R,5S)-5-(acetoxyamino)-4-hydroxy-3,6-dimethoxytetrahydro-2H-pyran-2-yl) methyl (16R)-3-(((2S,4S,5R)-4-methoxy-2,5-dimethyltetrahydro-2H-pyran-2-yl)oxy-10,13,16-trimethyl-17-(5-oxo-2,5-dihydrofuran-3-yl) hexadecahydro-14H-cyclopenta [a] phenanthren-14-yl) phthalate] (Chitosan-Ph-Oleander). This ligand and its complexes with several metals (Cr+3, Mn+2, Fe+3, Ni+2, Cu+2, Zn+2) were characterized using FTIR, UV-visible and 1H-NMR spectroscopy, as well as by molar conductivity, magnetic moment, and TGA analysis. The biological activity for the prepared polymer and its complexes was studied to inhibit the effectiveness of some bacteria found in polluted water taken from hospitals wastewater. The effectiveness of inhibition was tested on Fusarium oxysporum fungus, which causes wilting, rotting and seedling death diseases in various types of plants. The elemental and spectral investigation results showed that all prepared compounds had octahedral geometry. Compared to the free ligand, all metal complexes showed discernible antibacterial activity. The zinc(II) complex, in comparison to other metal complexes, showed higher antibacterial activity against Faecal streptococci bacteria (G+) and Pseudomonas aeruginosa bacteria (G−). In addition, the inhibition rate of the effectiveness of the F. oxysporum fungus reached 50%.